Integrated Weed Management Strategies in Cover Crop–based, Organic Rotational No-Till Corn and Soybean in the Mid-Atlantic Region. Issue 1 (21st September 2017) - Wallace, John M.; Keene, Clair L.; Curran, William; Mirsky, Steven; Ryan, Matthew R.; VanGessel, Mark J.
Abstract : Cover crop–based, organic rotational no-till (CCORNT) corn and soybean systems have been developed in the mid-Atlantic region to build soil health, increase management flexibility, and reduce labor. In this system, a roller-crimped cover crop mulch provides within-season weed suppression in no-till corn and soybean. A cropping system experiment was conducted in Pennsylvania, Maryland, and Delaware to test the cumulative effects of a multitactic weed management approach in a 3-yr hairy vetch/triticale–corn–cereal rye–soybean–winter wheat CCORNT rotation. Treatments included delayed planting dates (early, intermediate, late) and supplemental weed control using high-residue (HR) cultivation in no-till corn and soybean phases. In the no-till corn phase, HR cultivation decreased weed biomass relative to the uncultivated control by 58%, 23%, and 62% in Delaware, Maryland, and Pennsylvania, respectively. In the no-till soybean phase, HR cultivation decreased weed biomass relative to the uncultivated treatment planted in narrow rows (19 to 38 cm) by 20%, 41%, and 78% in Delaware, Maryland, and Pennsylvania, respectively. Common ragweed was more dominant in soybean (39% of total biomass) compared with corn (10% of total biomass), whereas giant foxtail and smooth pigweed were more dominant in corn, comprising 46% and 22% of total biomass, respectively. Common ragweed became less abundant as corn and soybean planting dates were delayed, whereas giant foxtail and smooth pigweed increased as a percentage of total biomass as planting dates were delayed. At the Pennsylvania location, inconsistent termination of cover crops with the roller-crimper resulted in volunteer cover crops in other phases of the rotation. Our results indicate that HR cultivation is necessary to achieve adequate weed control in CCORNT systems. Integration of winter grain or perennial forages into CCORNT systems will also be an important management tactic for truncating weed seedbank population increases.